Christianity in South and Central Asia - Ross, Kenneth R.; Jeyaraj, Daniel; Johnson, Todd M. (Todd Michael), 1958- (Edinburgh companions to global Christianity., 2019)
This reference volume covers every country in South and Central Asia, offering reliable demographic information and original interpretative essays by Indigenous scholars and practitioners.